Differential Pulse Voltammetric (DPV) Determination of Phosphomolybdenum Complexes by a Poly(Vinyl Chloride) Coated Molybdenum Blue Modified Pencil Graphite Electrode (PVC-MB-PGE) - Arvas, Melih Besir; Gorduk, Ozge; Gencten, Metin; Sahin, Yucel (TAYLOR & FRANCIS INC, 2021)
The rapid and accurate determination of phosphate is necessary for human health and the environment. In this study, three species of inorganic phosphate were sensitively determined by the use of poly(vinyl chloride) (PVC)-coated molybdenum blue (MB) modified pencil graphite electrodes (PGEs) for the first time. The prepared electrodes were characterized by electrochemical and microscopic methods. For the determination of inorganic phosphate species, PMo12O43-, PMo(11)O(39)H(4)(7-)and PMo(10)O(38)H(8)(11-)complexes were formed by the interaction of molybdenum blue and phosphate under the optimized conditions. Peaks observed in the differential pulse voltammograms (DPVs) were due to the PO43-, HPO(4)(2-)and H(2)PO(4)(-)complexes and the number of molybdenum atoms in molybdenum blue. For the electrochemical determination of these complexes, each had an oxidation peak at a distinctive potential in the differential pulse voltammograms. The electrodes also showed good selectivity for the different phosphate species since they formed unique complex structure with phosphate species. The limits of detection and quantitation were determined to be 0.141 mu M and 0.47 mu M for PO43-(PMo10O38H811-), 0.11 mu M and 0.334 mu M for HPO42-(PMo12O403-), and 0.129 mu M and 0.432 mu M for H2PO4-(PMo11O39H47-), respectively.
Keywords: Differential pulse voltammetry (DPV); molybdenum blue; molybdophosphate complexes; phosphate ions; poly(vinyl chloride) coated modified pencil graphite electrode (PVC-MB-PGE); ELECTROCHEMICAL SENSOR; PHOSPHATE DETECTION; PYRUVATE OXIDASE; ONE-STEP; PHOSPHORUS; MOLYBDOPHOSPHATE; TEMPERATURE; ENVIRONMENT; PARAMETERS; SPECIATION; Chemistry